2022
DOI: 10.3390/life12071078
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial Treatment of Lung Cancer

Abstract: Purpose: The treatment efficacy of the transarterial approach to lung cancer is evaluated. Materials and Methods: A total of 98 patients with advanced lung cancer or recurrent lung cancer after the standard therapies were enrolled retrospectively. The bronchial arteries and mediastinal branches from the subclavian artery were selected by a microcatheter. Immediately after the selective arterial infusion of anti-neoplastic agents, embolization with a spherical embolic material was carried out. Local tumor effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…It has (Papaporfyriou A, Domayer J, Meilinger M, et al, 2021;Ozdemir C, Sokucu SN, Berk A, et al, 2019) been reported that bronchoscopic interventional therapy for endovascular tumor elimination can achieve a higher long-term survival of patients. Hori et al (2022) have also suggested that trans arterial intervention for lung cancer should be considered as a viable treatment option. Bronchoscopic interventional Therapy, especially Photodynamic Therapy (PDT), can achieve radical curative effect on early invasive cancer and low grade malignancy, and may become a treatment method (Ikeda N, Usuda J & Maehara S, 2020) that can replace surgery.…”
Section: Progress In the Application Of Interventional Therapy In Pat...mentioning
confidence: 99%
“…It has (Papaporfyriou A, Domayer J, Meilinger M, et al, 2021;Ozdemir C, Sokucu SN, Berk A, et al, 2019) been reported that bronchoscopic interventional therapy for endovascular tumor elimination can achieve a higher long-term survival of patients. Hori et al (2022) have also suggested that trans arterial intervention for lung cancer should be considered as a viable treatment option. Bronchoscopic interventional Therapy, especially Photodynamic Therapy (PDT), can achieve radical curative effect on early invasive cancer and low grade malignancy, and may become a treatment method (Ikeda N, Usuda J & Maehara S, 2020) that can replace surgery.…”
Section: Progress In the Application Of Interventional Therapy In Pat...mentioning
confidence: 99%